2021
DOI: 10.1155/2021/6669075
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Novel Insights into the Molecular Features and Regulatory Mechanisms of Mitochondrial Dynamic Disorder in the Pathogenesis of Cardiovascular Disease

Abstract: Mitochondria maintain mitochondrial homeostasis through continuous fusion and fission, that is, mitochondrial dynamics, which is precisely mediated by mitochondrial fission and fusion proteins, including dynamin-related protein 1 (Drp1), mitofusin 1 and 2 (Mfn1/2), and optic atrophy 1 (OPA1). When the mitochondrial fission and fusion of cardiomyocytes are out of balance, they will cause their own morphology and function disorders, which damage the structure and function of the heart, are involved in the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 95 publications
(119 reference statements)
0
13
0
Order By: Relevance
“… 96 100 The fusion of the mitochondrial membrane includes the outer membrane fusion, which is induced by mitofusin 1 (MFN1) and mitofusin 2 (MFN2), and the inner membrane fusion induced by optic atrophy 1 (OPA1). 99 , 100 It was reported that MFN1 and MFN2 are localized on the OMM and ER membrane and exist as homo- or heterodimers that function to induce the membrane fusion of mitochondria. 101 , 102 It has also been reported that these GTPases function to construct mitochondria-ER tethering sites for Ca 2+ transport.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 96 100 The fusion of the mitochondrial membrane includes the outer membrane fusion, which is induced by mitofusin 1 (MFN1) and mitofusin 2 (MFN2), and the inner membrane fusion induced by optic atrophy 1 (OPA1). 99 , 100 It was reported that MFN1 and MFN2 are localized on the OMM and ER membrane and exist as homo- or heterodimers that function to induce the membrane fusion of mitochondria. 101 , 102 It has also been reported that these GTPases function to construct mitochondria-ER tethering sites for Ca 2+ transport.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The increased fusion or decreased fission promotes the formation of an extended mitochondrial network, and the decreased fusion or increased fission leads to the fragmentation of mitochondria [39]. The imbalance of mitochondrial fusion and fission played a key role in the mechanism for myocardial injury in diabetes mellitus [10,40]; mitochondrial dysfunction seems to be an important target for therapy to improve 14 Oxidative Medicine and Cellular Longevity cardiac function directly [41]. After abnormal glycolipid exposures, we observed that the mitochondrial membrane potential and intracellular ATP concentration were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctions in mitochondrial dynamics have a central role in the development of AKI and cardiovascular diseases, since excessive fission and low fusion are detrimental to both tissues [ 9 , 55 , 56 ]. A large number of studies indicated that OPA1 and Mfn 2 may suffer post-transcriptional and translational modifications, reducing their expression in kidney diseases [ 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%